The Implementation of Dijkstra Algorithm in Searching the Shortest Path for Fire Engines in Medan City - Sidabutar, Juni Artha; Sinulingga, Ujian (Talenta Publisher, 2022)
Dijkstra algorithm is one of the algorithms to determine the shortest path from one vertex to another. In this study, the authors examine the shortest path that fire engines can choose from at the Regional I Fire Unit Post and Region II Fire Unit Post to the most densely populated villages that predict fires, namely Tegal Sari I Village, Sari Rejo Village and Kampung Baru Village. The results obtained are that if a fire occurs in the Tegal Sari I and Sari Rejo Villages, the Regional I Fire Unit which has the closest distance with the shortest route length is 5.16 km and 7.28 km, while if a fire occurs in Kampung Baru Village, the Regional Fire Unit is II which has the closest distance with the shortest route length of 5.32 km.